Livestock production in central Mali: The "Mouton de Case" system of smallholder sheep fattening - Kolff, H.E.; Wilson, R.T. (Elsevier, 1985)
Presents results of studies to characterize & define the 'Mouton de Case' intensive sheep fattening system in Central Mali, viz. ownership patterns, management and feeds & feeding systems in two agro-pastoral subsystems in Niono area; growth rates & weights of sheep; costs, benefits, motivation & production problems; price/weight/age relationships of sheep on sale and effects of 'tabaski' on sale & slaughter patterns.